ANALISIS KESALAHAN KONSEP MAHASISWA CALON GURU FISIKA PADA MATERI KINEMATIKA MENGGUNAKAN TES DIAGNOSTIK THREE TIER - Alfrie Musa Rampengan; Kristanto Gunawan Kumonong; Anneke Tinneke Rondonuwu (Charm Sains: Jurnal Pendidikan Fisika, 2021)
Misconception is a wrong way of looking at an event that occurs. Various types of research have also been conducted to uncover and resolve these misconceptions. This study aims to analyze the misconceptions of the Physics Teacher Candidate Student (MCGF) on the concept of kinematics. With the form of qualitative research, the data collection technique was carried out using a three-level diagnostic test while the validity of the data used reference material, namely a test recap in the form of a three-level diagnostic test result script. Data analysis was carried out by being described, categorized, synthesized, then sorted systematically using three steps, namely editing, presenting, and drawing conclusions. From the researc, the results show that the misconceptions that occur in MCGF are determined by the sub-concept of Regularly Changing Straight Motion (GLBB) and Parabolic Motion, especially in determining the projectile trajectory. Factors that cause misconceptions are associative thoughts, incomplete reasoning and even tend to be wrong, and wrong intuition. An alternative solution that can be done is exposing the respondent to recovery, anomalous events, and incomplete and erroneous rationality and reasoning so that it is immediately completed. It is hoped that any misconceptions that occur can be immediately contacted.